Morphometric sexing of little spiderhunter (Arachnothera longirostra) in Peninsular Malaysia - Puan, Chong Leong; Ng, Wei Lun; Yong, Christina Seok Yien; Abdl Jalil, Norehan (Universiti Putra Malaysia Press, 2018)
Sexual dimorphism is often directly linked to sexual selection, mating systems and resource partitioning, which are crucial in species conservation and management. Many avian species, including pollinator birds, are sexually dimorphic with respect to size and colour, yet, such differences may be subtle for some species. In this study, molecular sexing was performed in addition to determining morphological parameters that can aid in future sex determination of a common forest pollinator, the little spiderhunter (Arachnothera longirostra), in Peninsular Malaysia. Based on 23 captures made in four forests, two out of seven body measurements (i.e. wing and tail lengths) were useful in predicting the sexes of the bird with 100% accuracy. In addition, significant differences were found in the head, bill, and total body lengths. Such findings will facilitate more effective sex identification in future field studies, particularly in the case of juveniles.